Intrinsic Valley Polarization in Computationally Discovered Two‐Dimensional Ferrovalley Materials: LaI2 and PrI2 Monolayers. Issue 4 (19th January 2022) - Sharan, Abhishek; Singh, Nirpendra
Abstract: Ferrovalley materials with intrinsic valley polarization present a novel space for materials exploration suitable for valleytronic applications. Here, two Ferrovalley materials, LaI2 and PrI2 monolayers, exhibiting intrinsic valley polarizations of 28 and 35 meV, respectively, mediated by strong magnetic exchange interaction and spin‐orbit coupling are computationally discovered. The unconstrained crystal structure prediction algorithm is used to predict the structures of bulk LaI2 and PrI2, which are layered and analogous to the 2H phase of transition metal dichalcogenides. The monolayers have small exfoliation energy (smaller than MoS2 ) and exhibit dynamical, mechanical, and thermodynamical stability, advocating their experimental realization. Valley polarization under the effect of bi‐axial strain is preserved and can be used to enhance valley splitting. Finally, the anomalous hall properties of both the monolayers under the effect of in‐plane electric field are discussed. Both the materials exhibit significant anomalous Hall conductivity with proper tuning of the Fermi level. Abstract : Ferrovalley materials are promising candidates for valleytronics. The crystal structure search algorithm is used to discover two‐dimensional materials, LaI2 and PrI2 monolayers, which exhibit intrinsic ferromagnetism and valley polarization of 28 meV and 35 meV, respectively. These materials are stable under strain, and valley splitting is preserved. Anomalous Hall properties of these materials are further discussed for experimental realization.